2007
DOI: 10.1007/s11547-007-0204-y
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of collagen meniscus implants by MRI

Abstract: MRI enables morphological and structural changes of CMI to be monitored over time. Follow-up can be extended beyond 2 years, until the CMI has stabilised and subchondral bone marrow oedema has completely resolved. In the single case with a poor CMI outcome, no related direct or indirect signs were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 22 publications
5
95
4
2
Order By: Relevance
“…7 and 8). Genovese et al (2007) developed an MRI score in order to assess the signal intensity and size of the scaffold. Various reports have shown that the scaffold tends to reduce its size over time, with a consistent reduction after 1 year that slowly progresses until 10 years.…”
Section: Magnetic Resonance Imaging Findingsmentioning
confidence: 99%
“…7 and 8). Genovese et al (2007) developed an MRI score in order to assess the signal intensity and size of the scaffold. Various reports have shown that the scaffold tends to reduce its size over time, with a consistent reduction after 1 year that slowly progresses until 10 years.…”
Section: Magnetic Resonance Imaging Findingsmentioning
confidence: 99%
“…Firstly, the size of the CMI® reduced during follow-up [27][28][29]. Secondly, the signal intensity does not resemble that of the native meniscus, either for short follow-up [27,28] or for follow-up periods exceeding ten years [26,29].…”
Section: Partial Meniscal Substitutesmentioning
confidence: 99%
“…Signal intensity of the implant is distinct from native meniscus tissue. Reprinted from [28] much from the control patients in the CMI® study, only a proper randomised controlled study could support the additional value of the Actifit® implant.…”
Section: Partial Meniscal Substitutesmentioning
confidence: 99%
“…Bessere Aussagekraft bietet dabei eine MRT-Untersuchung. Entsprechende Kriterien zur Beurteilung des eingebrachten Implantats wurden von Genovese et al [18] festgelegt (. Tab.…”
Section: Introductionunclassified